Improving mechanical and water sorption properties of thermoplastic starch by incorporating chitosan filler. (September 2021) - Balla, Bence; Bartos, András; Kun, Dávid; Csiszár, Emília; Móczó, János; Fekete, Erika
Abstract: To develop an adequate matrix polymer for agricultural or packaging applications, thermoplastic starch (TPS)/chitosan composites were prepared in a wide composition range either by injection moulding or in an internal mixer followed by compression moulding. Chitosan behaves as filler forming dispersed structure in TPS samples prepared by thermomechanical methods without any additional acid. In the TPS composites chitosan has a considerable reinforcing effect. Regardless of the production methods, the Young's modulus and tensile strength increase significantly. Furthermore, addition of chitosan has a considerable effect on the water sorption of TPS-based composites. Chitosan slightly decreases the maximum water uptake of composites and reduces significantly the water sorption rate especially in the samples prepared by injection moulding. Besides, chitosan can greatly reduce the shrinkage of injection moulded TPS composites and delay the appearance of mould on the surface even at high humidity. Highlights: Chitosan considerably increases the stiffness and strength of TPS. Chitosan acts as a filler in TPS products prepared by thermomechanical methods. Chitosan greatly reduces the shrinkage of injection moulded TPS composites. Chitosan affects the water sorption of TPS composites. Mould growing on TPS surface can be delayed by chitosan addition.